Development of a lean assessment tool and measuring the effect of culture from employee perception. Issue 7 (3rd March 2020) - Loyd, Nicholas; Harris, Gregory; Gholston, Sampson; Berkowitz, David
Abstract : Purpose: Few companies have had the success that Toyota Motor Corporation has experienced over the past 70 years. Many give credit for Toyota's success to the company's famous Toyota Production System. Companies outside of Toyota have tried to implement versions of Toyota's system as Lean production; however, few companies have experienced the success of Toyota, and none have experienced Toyota's sustained success. In 2001, Toyota released a publication entitled The Toyota Way 2001 as a set of globalized standards of the culture that drives the success of the Toyota Production System. Design/methodology/approach: This research examines the effect of the Toyota Way on the implementation of Lean production outside of Toyota. A survey was developed and a study was performed on a sample of 349 participants with Lean experience. Structural equation modeling was used to test the relationship between the Toyota Way culture, Lean production, and achieving the desired Lean production system results. Findings: The results of this research discovered that the existence of the Toyota Way culture has a significant and positive mediating effect on a Lean production system achieving the desired Lean results. Originality/value: This research created a validated survey instrument that can be used to evaluate and understand the status of a Lean implementation initiative based upon employee perception. The results of this study support assertions made by Lean practitioners and previous research stating that culture affects the level of success of Lean production system implementation. While this may not seem like breaking news, prior to this study no statistically validated research supporting such an assertion could be found. Furthermore, this research defines culture very specifically as the Toyota Way culture as outlined in The Toyota Way 2001 .